(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examines the Digawa group in northern Nigeria, particularly in Jigawa State, known for their distinct beliefs and practices among Muslims. The research critically analyzes their history, divisions, and socio-economic impact to differentiate acceptable beliefs from those deemed rejected. Utilizing descriptive, analytical, field, and critical methods, the study references the sayings of Digawa leaders and Islamic Sharia texts. The Digawa are divided into praying (Qadiriyya and Mahdiyya) and non-praying sections, each with unique practices such as strict confinement of women, prohibition of music, and specific burial customs. The findings reveal significant deviations from mainstream Islamic scholarship, emphasizing the need for informed intervention to guide the Digawa towards more universally accepted practices. This analysis is supported by the Islamic principle of Ijtihad, which allows for interpretation and adaptation of Islamic teachings to ensure alignment with the core values and broader consensus within the Muslim ummah.